Using drawings to understand perceptions of civic engagement across disciplines: 'Seeing is understanding'. (May 2019) - Feeney, Sharon; Hogan, John
In this article, we wish to investigate if disciplinary differences exist among students when considering the topic of civic engagement. We use freehand drawing to create a learning environment in the classroom wherein students can seek to develop meaningful associations with civic engagement. The drawings examined here, produced by three different class groups, provide insights into how young adults perceive their society and their place in it, and thus communicate their understanding of civic engagement. Freehand drawing, in bypassing cognitive verbal processing routes, leads students to produce clearer and more holistic images. It allows them to put into visuals a level of comprehension that is sometimes difficult for them to articulate with words. This use of the visual method can help students to identify the tacit knowledge that they already possess.